Technological specialisation courses in Portugal: description and suggested improvements - Nunes da Costa, Nilza Maria Vilhena [Verfasser]; Simões, Ana Raquel [Verfasser]; Pereira, Giselia Antunes [Verfasser]; Pombo, Lúcia [Verfasser] (My University, 2009)
"This study is a part of the 'Post-secondary Vocational Training in Portugal Project: from a description through to suggestions to improve training quality', which ran from 2003 to 2006. This article, which makes use of data obtained from interviews with Directors of Schools which offer technological specialisation courses (CETs) and from questionnaires answered by trainers and trainees, describes the courses currently available in the central region of Portugal and identifies the strengths and weaknesses of this type of training. The positive aspects identified are: the type of training; interpersonal relationships, the developments of trainees' skills and the benefits to the institutions. The aspects requiring improvement are: course organisation (coordination and logistic matters) and some curricular aspects. Some measures to improve the quality of CETs are suggested, which would assist the creation of courses, strengthen the collective image of this type of training and link training evaluation to training quality." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5 Weiterbildung; L 1 Curricula & Lehrpläne; L 6 Qualität; I 2.2.1 Westeuropa; Berufsausbildung; Technische Bildung; Curriculum; Qualität; Empirische Untersuchung; Portugal